The appearance (Schein) in the Lectures on aesthetics of G. W. F. Hegel - Vanegas Zubiría, Carlos Mario (Estudios de Filosofía, 2016)
It may be noted that since Plato art has been philosophically undermined because its element and its means (media) is appearance. In such a way that, being and truth according to ancient theory, are found in ideas rather than in sensible appearances. Hegel is far from Platonism in his Lectures on aesthetics and on the contrary, he makes a claim of the appearance in art. The interest of this paper is to investigate the distinction between deceiving appearance linked to non-being, and the necessary appearance of works of art, that for Hegel, is the appearance of the essence. The article uses both the opposition raised by Hegel between natural beauty and spiritual beauty, as the way of being of art as an ideal, to indicate that the appearance of art is one of the ways in which the spirit reaches concretion, where it reveals its active consciousness, its reasoning, and can manifest determinations and significantly higher interests for its culture.